Recovery of Fine Gold Particles Using a Falcon 'B' Separator - S. Gregory (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
Many gold treatment plants have sulphides and coarse particle gangue components that contain gold in their tailings (cyanide leach residues and flotation tailings). Coarse and very fine liberated gold may also be present in some tailings streams. Two issues usually govern the economics of recovering additional gold from gold occluded in sulphide and gangue particles. The liberation characteristics of the gold in the sulphide and coarse gangue (gold liberation versus grind size) is the first and most important of the two. If fine grinding can liberate a reasonable amount of the gold, then the next important issue is how effectively these two constituents can be concentrated. Flotation will achieve high sulphide recovery but is usually costly. Selectivity is also an issue because of entrainment. Continuous centrifugal gravity concentration offers a viable solution to the recovery of both sulphides and coarse gangue however selectivity is also likely to be a problem. The possibility of improving concentrate grade by using a Falcon B separator was investigated. This paper describes a program of test work carried out on a gold leach tailings using a laboratory Falcon '13' separator. The program involved three different bowl angles: 10, 12 and 14 degrees and two bowl speeds (giving 250 and 350G accelerations). A number of tests were also performed on samples that had free gold present to ascertain the size-by-size recovery of gold in these samples.